The Effect of Student’s Mix Marketing Services on Student's Interest in Saving at Syari’ah Bank - Muhammad Hilman Fikri; Abd. Rasyid Syamsuri; Julianto Hutasuhut; Ardansyah Harahap; Solawati Nainggolan (Budapest International Research and Critics University, 2022)
This study aims to determine and analyze how much the influence of mixmarketing service on students' interest in becoming customers at Syari’ah banks. In finding out which variable is the most dominant, this type of research is quantitative research. This research used numerical data and analyzed through statistics. The data collection in this study used a questionnaire. Questionnaires were distributed directly to students who were the objects of this research. The population in this study were students of the Economics Faculty, Alwasliyah Medan, totaling 260 people. Based on calculations using the Slovin formula, the sample obtained was 158.The questionnaire given using the Likert scale measurement basic scale. Data were analyzed using validity and reliability tests, classical assumption test, multiple regression analysis (correlation coefficient test, coefficient of determination test), F test and T test with the help of SPSS software. The results of the study through the F test showed that the product, location, promotion, price, service quality variables simultaneously had a positive and significant effect on student interest in becoming customers at Syari’ah Banks. Meanwhile, the t-test results show that the product, promotion and price variables have no partial positive effect. While the variables Location and Service Quality have a positive and significant effect on student interest. The dominating variable, that is service quality, has a positive and significant effect on student interest in becoming customers.